Prevalence and Clinical Predictors of Insulin Resistance in Reproductive-Aged Thai Women with Polycystic Ovary Syndrome - Thanyarat Wongwananuruk; Manee Rattanachaiyanont; Suchada Indhavivadhana; Pichai Leerasiri; Kitirat Techatraisak; Prasong Tanmahasamut; Surasak Angsuwathana; Chongdee Dangrat (International Journal of Endocrinology)
Objectives. To determine the prevalence of insulin resistance (IR) and its predictors in reproductive-aged Thai women with polycystic ovary syndrome (PCOS). Methods. A cross-sectional study was conducted from May 2007 to January 2009. Participants were 250 Thai women with PCOS. Information regarding medical history and physical examination and results of 75 gram OGTT were recorded. Results. The overall prevalence of IR was 20.0%, comprising the prevalence of impaired fasting glucose, impaired glucose tolerance, and diabetic mellitus of 3.2%, 13.6%, and 5.6%, respectively. Multiple logistic regression analysis showed that the independent predictors for IR were age of ≥30 years old, waist circumference (WC) of ≥80 cm, presence of acanthosis nigricans (AN), and dyslipidemia with odds ratios (95% confidence interval) of 2.14 (1.01–4.52), 3.53 (1.28–9.75), 2.63 (1.17–5.88), and 3.07 (1.16–8.11), respectively. Conclusion. The overall prevalence of IR in reproductive-aged Thai women with PCOS is 20.0%. Age ≥30 years old, WC ≥80 cm, the presence of AN, and dyslipidemia are the significant clinical predictors.